2008
DOI: 10.1017/s0003598x00097647
|View full text |Cite
|
Sign up to set email alerts
|

Tanged points, microblades and Late Palaeolithic hunting in Korea

Abstract: The present study examines the stone weapons available in Late Palaeolithic Korea, showing how the change in lithics signals a change in hunting strategy. In advance of the Late Glacial Maximum, a tanged spear tip flourished, reflecting the hunting of large mammals associated with the colder climate. In the more variable climate that followed, the prevalence of microliths suggests lightweight composite hunting weapons mostly used in pursuit of small game and diverse food resources. These weapons eventually inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 24 publications
1
16
0
1
Order By: Relevance
“…On a related note regarding the Seong (2008Seong ( , 2009) argument, is that there is something to be said about making arguments about hominin subsistence patterns through the presence of certain types of stone tools. Indeed, Shea (2007: 226) recently justifiably observed that "recognizing the role that variability may have played in Early Paleolithic stone-tool design is a significant step toward more realistic models of early hominin subsistence".…”
Section: In Situ Evolution Modelmentioning
confidence: 99%
See 2 more Smart Citations
“…On a related note regarding the Seong (2008Seong ( , 2009) argument, is that there is something to be said about making arguments about hominin subsistence patterns through the presence of certain types of stone tools. Indeed, Shea (2007: 226) recently justifiably observed that "recognizing the role that variability may have played in Early Paleolithic stone-tool design is a significant step toward more realistic models of early hominin subsistence".…”
Section: In Situ Evolution Modelmentioning
confidence: 99%
“…Based on current evidence in Korea, this is the period when the Early to Late Paleolithic transition occurs and a time when the climate shifts from a relatively warm to a colder environment. The environmental framework is particularly important because neither of the earlier models (but see Seong (2008) for some discussion) appeared to place much importance on it. Although it is difficult to necessarily associate a specific hominin taxon with a specific stone tool type [e.g., see difficulties with trying to determine who the first stone toolmakers were (Toth and Schick, 2009)], it will still be a useful exercise to see if pertinent variation is present in the hominin fossil record.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Stemmed and shouldered points have been found in Upper Paleolithic sites on the Korean Peninsula dated from over 35,000 to 15,000 years ago, some associated with blades and others with microblades (Seong 2008 ). The Korean points are often thin, with relatively long stems, but most are made on fl akes with only marginal retouch.…”
Section: Northeast Asiamentioning
confidence: 99%
“…Worldwide, quartz was used as a raw material for stone tools (Flenniken 1981;Taçon 1991;Saville and Ballin 2000;Gao and Norton 2002;Plew 2003;Seong 2008) and in many regions quartz was the dominant raw material, if not the only raw material (Barber 1981;Knutsson 1988;Bisson 1990;Cornelissen 2003). This was undertaken in order to understand how vein quartz artefacts are identified and classified by people with different skill levels in lithic analysis.…”
Section: Introductionmentioning
confidence: 99%